ANALISIS PREDIKSI HARGA SAHAM MICROSOFT CORPORATION SELAMA MASA KETIDAKSTABILAN EKONOMI GLOBAL - Rakhmawati, Desty (Gapenas Publisher, 2025)
Global economic instability, influenced by geopolitical turmoil, high inflation, and financial market pressures. This uncertainty can affect global stock price fluctuations, including MSFT shares. This study aims to analyze and predict MSFT's share price during periods of global economic instability using the ARRIMA time series approach. The data used for the analysis was 753 daily historical data on the closing price of MSFT shares. Based on the results of the stationary test using ADF, the data is non-stationary at the level, and becomes stationary after differentiating once. The best model for data was obtained from the ARIMA model (0,1,0) and obtained an AIC value of 4633,602, an RMSE of 11.20, showing quite good prediction results. The prediction results show that the MSFT share price prediction is close to USD 419 to USD 420. The results of this prediction can be used as a reference in understanding the movement of MSFT shares for investors during periods of global uncertainty.